A Cross-Cultural Study of Japanese & American Culture - Meg Baker; Charlotte Streit; Kimberly Wade (WOW Stories, 2011)
This vignette explores a classroom's cross-cultural study using global literature as a means to build intercultural awareness and understanding for the students by comparing and contrasting Japanese and American culture. The books provided from the Spokane Literacy Community allowed students to critically engage with stories centered on or in Japan and interact with a foreign culture within a classroom setting.